2017
DOI: 10.3390/a10020049
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Statistical Process Control Using Enhanced Bottleneck Neural Network

Abstract: Abstract:Monitoring process upsets and malfunctions as early as possible and then finding and removing the factors causing the respective events is of great importance for safe operation and improved productivity. Conventional process monitoring using principal component analysis (PCA) often supposes that process data follow a Gaussian distribution. However, this kind of constraint cannot be satisfied in practice because many industrial processes frequently span multiple operating states. To overcome this diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…This is because of the similarity of PWRMSE parameter for total suspended solids GEV and GMM distributions. The possibility of using Gaussian Mixture Model (GMM) for the assessment of the operation work of the wastewater treatment plant was also presented by Yu [52] and Bouzenad and Ramdani [53]. The results of the analysis performed using PWRMSE parameter turned out to be compatible with the results of Anderson-Darling (A-D) test.…”
Section: Selection Of the Best-fitting Statistical Distributionmentioning
confidence: 63%
“…This is because of the similarity of PWRMSE parameter for total suspended solids GEV and GMM distributions. The possibility of using Gaussian Mixture Model (GMM) for the assessment of the operation work of the wastewater treatment plant was also presented by Yu [52] and Bouzenad and Ramdani [53]. The results of the analysis performed using PWRMSE parameter turned out to be compatible with the results of Anderson-Darling (A-D) test.…”
Section: Selection Of the Best-fitting Statistical Distributionmentioning
confidence: 63%
“…The authors of the cited paper [19] also showed that GMM distribution is the best for pollutant indicator value descriptions. The possibility of using GMM distribution for the control of WWTP operation work has been presented by Bouzenad and Ramdani [43] and Yu [44] too. Table 3 shows that for BOD 5 , the best-fitted theoretical distribution in raw sewage was GEV distribution, while for the sewage after mechanical treatment and biological treatment, it was GMM distribution.…”
Section: Selection Of the Best-fitted Probability Distributionmentioning
confidence: 99%
“…The authors of the cited paper [19] also showed that GMM distribution is the best for pollutant indicator value descriptions. The possibility of using GMM distribution for the control of WWTP operation work has been presented by Bouzenad and Ramdani [43] and Yu [44] too.…”
Section: Selection Of the Best-fitted Probability Distributionmentioning
confidence: 99%
“…To reduce the dimensions, G1, G2 and G3 are first equally divided into 12 sub-blocks with 64 × 8 dimensions. The principal component analysis method [33] is used to reduce the dimension of 12 sub-blocks to 64 × 1 dimensions, which is 64 feature points. The average value of 64 feature points is calculated as the feature value of each sub-block.…”
Section: Haar + Bpmentioning
confidence: 99%